2016
DOI: 10.1590/s0102-865020160110000002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of passive tobacco smoking on the microcirculation of the abdominal wall in rats

Abstract: Brazil. Scientific, intellectual, conception and design of the study; analysis and interpretation of data, critical revision, final approval. ABSTRACT PURPOSE:To analysis the effects of passive smoking on the microstructure of tissues of the abdominal wall regarding microcirculation, using histopathological study of the tobacco exposed rats. METHODS: Twenty four male Wistar rats were divided in Control Group (CG = 8 animals) and Exposition Groups (EG = 16 animals).EG was exposed to cigarette smoke 4x/day for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Eventually,TE can result in plaque and blood clots, blood flow restriction, as well as heart attacks and strokes. Similar to heart disease, strokes have a high risk of death and stroke survivors may experience disastrous disabling conditions, including paralysis or the loss of vision or speech [9][10][11]. Several epidemiological studies have concluded that smoking is a major cause of CVD and is the cause of a quarter of deaths from CVD [12].…”
Section: Introductionmentioning
confidence: 99%
“…Eventually,TE can result in plaque and blood clots, blood flow restriction, as well as heart attacks and strokes. Similar to heart disease, strokes have a high risk of death and stroke survivors may experience disastrous disabling conditions, including paralysis or the loss of vision or speech [9][10][11]. Several epidemiological studies have concluded that smoking is a major cause of CVD and is the cause of a quarter of deaths from CVD [12].…”
Section: Introductionmentioning
confidence: 99%
“… 41 Local complications such as hematoma, seroma, wound dehiscence, and skin necrosis are recorded in 52% smokers and 32% nonsmokers. 42 46 In our series, 64.3% were smokers. However, wound complications were <3%.…”
Section: Discussionmentioning
confidence: 43%
“…Free radicals may originate from: (1) gases or tar in cigarette smoke, (2) circulating or in situ-activated macrophages and neutrophils, (3) endogenous sources of reactive oxygen species such as uncoupled eNOS and the mitochondrial electron transport chain. The free radicals, such as superoxide, reacted with NO, this not only reduced the utilization of NO, but also produced peroxide nitrite, which further enhanced oxidative stress in cells [14,15].…”
Section: Discussionmentioning
confidence: 99%